Implementation of Local Potential-Based Science Learning at Krakal 1 Public Elementary School, Alian, Kebumen - Makfiyah, Rofi’; Chasna, Tanaaliina; Soniawati, Nabila Dwi; Khilfah, Lia Nur; Zahra, Umu Adilah; Sofa, Nofi Maulana; Subekti, Septiani; Handayani, Ratna; Fatimah, Siti; Trisnawati, Oky Ristya; Mustajab, Mustajab (Proceeding International Conference on Religion, Science and Education, 2026)
This study aims to analyze the implementation of local potential-based science learning at Krakal 1 Public Elementary School using a phenomenological qualitative approach. Data collection techniques include interviews, observation, and documentation, which are then analyzed using the Miles, Huberman, and Saldana model, including data condensation, data presentation, and data verification. Science education based on local potential utilizes both natural resources (SDA) and human resources (SDM) available around the school. The results of the study show that the integration of local potential, such as agriculture and the tofu industry, makes learning more contextual and meaningful. Despite challenges in the form of time and cost constraints, the utilization of local potential has an impact on increasing student enthusiasm, collaboration, communication, activity, and critical thinking skills. Therefore, science learning based on local potential needs to be developed to provide a learning experience that is relevant and applicable in the community.